2019
DOI: 10.1111/bcp.14039
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of tadalafil in a paediatric population with pulmonary arterial hypertension: A multiple ascending‐dose study

Abstract: AimsTo evaluate the pharmacokinetics and safety of once‐daily (QD) tadalafil in paediatric patients with pulmonary arterial hypertension (PAH) to establish an appropriate dose range for further research.MethodsThis was an open‐label, multicentre, international, multiple‐ascending‐dose study. Patients aged ≥2 years were enrolled into 1 of 3 cohorts based on body weight: heavy‐weight (≥40 kg), middle‐weight (25 to <40 kg), and light‐weight (<25 kg). Each patient received tadalafil QD for 10 weeks: 5 weeks at a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 15 publications
3
28
0
1
Order By: Relevance
“…13 Recent pharmacokinetic studies have shown adult exposure levels can be obtained in children and tadalafil levels are lower in combination with bosentan, but remain in the expected range. 7 The overall safety profile of tadalafil, including most common TEAEs, observed in the current study was consistent with previous knowledge. The overall incidence of AEs was higher in the tadalafil group compared with placebo.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…13 Recent pharmacokinetic studies have shown adult exposure levels can be obtained in children and tadalafil levels are lower in combination with bosentan, but remain in the expected range. 7 The overall safety profile of tadalafil, including most common TEAEs, observed in the current study was consistent with previous knowledge. The overall incidence of AEs was higher in the tadalafil group compared with placebo.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Small et al. (2019) 7 recently also reported tadalafil 40 mg QD for patients ≥40 kg, and 20 mg QD for patients <40 kg and ≥2 years old have an acceptable safety profile in pediatric patients with PAH consistent with the safety profile in adult patients with PAH. 4 …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A phase Ib/II, multiple ascending dose study (H6D-MC-LVIG [LVIG]) [5] was conducted to evaluate the safety and pharmacokinetics (PK) of tadalafil in planned PAH patients aged 6 months to < 18 years, with a goal to mimic typical drug exposures in adults with PAH and determine doses for further investigation in phase III. A previous publication discussed safety and noncompartmental analyses for this trial [5], whereas the focus of this article is on the results of the population PK (PopPK) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A phase Ib/II, multiple ascending dose study (H6D-MC-LVIG [LVIG]) [5] was conducted to evaluate the safety and pharmacokinetics (PK) of tadalafil in planned PAH patients aged 6 months to < 18 years, with a goal to mimic typical drug exposures in adults with PAH and determine doses for further investigation in phase III. A previous publication discussed safety and noncompartmental analyses for this trial [5], whereas the focus of this article is on the results of the population PK (PopPK) analysis. The purpose of the PopPK analysis was to characterize tadalafil PK across the range of body weights and ages enrolled in the study and in each cohort; to evaluate the effect of various covariates such as age, body weight, sex, and endothelin receptor antagonist (ERA) use on tadalafil exposure; and to predict appropriate dose(s) in subsequent pediatric studies of tadalafil.…”
Section: Introductionmentioning
confidence: 99%